Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Solve 3sqrt(x) = 8/(sqrt(9x - 32)) + sqrt(9x - 32)​

Sagot :

[tex] \huge \color{gray}{ \tt{answer}}[/tex]

[tex]x = 4[/tex]

Step-by-step explanation:

[tex]3 \sqrt{x} = \frac{8}{(9x - 32)} + \sqrt{(9x - 32)} [/tex]

  • move the expression to the left

[tex]3 \sqrt{x} - \frac{8}{ \sqrt{9x - 32} } - \sqrt{9x - 32} = 0[/tex]

  • transform the expression

[tex] \frac{3 \sqrt{(9x - 32 x)} - 8 - \sqrt{9x - 32} }{ \sqrt{9x - 32} } [/tex]

  • set the numerator

[tex]3 \sqrt{(9x - 32)x} - 8 - (9x - 32) = 0[/tex]

  • remove the parentheses

[tex]3 \sqrt{9 {x}^{2} - 32x} + 24 - 9x = 0[/tex]

  • move the expression to the right

[tex]3 \sqrt{9 {x}^{2} - 32x } - 24 + 9x[/tex]

  • divide both sides

[tex] \sqrt{9 {x}^{2} - 32x } = - 8 + 3x[/tex]

  • simplify the expression

[tex]9 {x}^{2} - 32x = 9 {x}^{2} - 48x + 64[/tex]

  • cancel equal terms

[tex] - 32x = - 48x + 64[/tex]

  • move the variable to the left

[tex] - 32x = + 48x = 64[/tex]

  • collect like terms

[tex]16x = 64[/tex]

  • divide both sides

[tex] = \: \: x = 4[/tex]

  • check the solution

[tex]3 \sqrt{4} = \frac{8}{ \sqrt{9 \times 4 - 32} } + \sqrt{9 \times 4 - 32} [/tex]

  • simplify

[tex]6 = 6[/tex]

  • so the solution is

[tex]≈ \: \: x = 4[/tex]

[tex] \huge \color {cyan}{ \tt{hope \: \: it \: \: helps}}[/tex]

Answer:

Step-by-step explanation:

[tex]3\sqrt{x}=\frac{8}{\sqrt{9x-32}}+\sqrt{9x -32}\\\\\\3\sqrt{x}=\frac{8*\sqrt{9x-32}}{(\sqrt{9x-32})*(\sqrt{9x-32})}+\sqrt{9x-32}\\\\3\sqrt{x}=\frac{8*\sqrt{9x-32}}{9x-32}+\sqrt{9x-32}\\\\\\3\sqrt{x}=(\sqrt{9x-32})(\frac{8}{9x-32}+1)\\\\\frac{3\sqrt{x}}{\sqrt{9x-32}}=\frac{8+9x-32}{9x-32}\\\\\frac{3\sqrt{x}}{\sqrt{9x-32}}=\frac{9x - 24}{9x-32}\\\\Take \ square\\\\(\frac{3\sqrt{x}}{\sqrt{9x-32}})^{2}=(\frac{9x-24}{9x-32})^{2}\\\\\frac{9x}{9x-32}=\frac{(9x-24)^{2}}{(9x-32)^{2}}\\\\[/tex]

9x*(9x - 32) = (9x- 24)²

9x*9x - 9x*32 = 81x² - 2*9x*24 + 576

81x² - 288x = 81x² - 432x + 576

81x² - 288x - 81x² + 432x - 576 = 0

81x² - 81x² - 288x + 432x - 576 = 0

144x - 576 = 0

144x = 576

x = 576/144

x =4

We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.